Identification of degradation products in Aripiprazole tablets by LC-QToF mass spectrometry - Reddy, Gosula Venkat Rami; Kumar, Avvaru Praveen; Reddy, Bobba Venkateswara; Kumar, Poonam; Gauttam, Ham Dutt (European Journal of Chemistry, 2010)
This paper describes the separation, identification and proposed structures of the degradation products formed during degradation analysis of aripiprazole in its final dosage form by high performance liquid chromatography (HPLC) coupled with quadrupole time-of-flight mass spectrometry (QToF-MS). The drug product was subjected to stress conditions including acid, base, thermal, oxidation, humidity and photolytic degradations. Aripiprazole was found to be stable in all conditions except in thermal and peroxide degradations. The degradation impurities were first separated by HPLC and then identified using QToF mass spectrometry. QToF mass spectrometer provided high order of mass accuracy for unknown impurities and their fragment ions to explore the elemental composition. Based on the fragmentation pattern, the possible structures of the unknown impurities were proposed. To the best of our knowledge, there were no methods available to identify the impurities during degradation of aripiprazole tablets by liquid chromatography-mass spectrometry.